STRATEGI DAGANG DALAM PERSPEKTIF ETIKA BISNIS SYARI’AH (Studi Kasus Di Pasar Induk Pringsewu) - Dedi Irawan (STMIK Pringsewu, 2022)
This study aims to determine the trading strategy in the perspective of Islamic Business ethics in the Pringsewu Main Market. The research method used is qualitative research. The results of the study show that sellers have not applied business ethics that are in accordance with sharia, they more often apply ethics based on personal will in the pursuit of profit. This is influenced by educational and cultural factors. Education is one of the important factors in the formation of personality and ethics, especially in business activities. Culture can also lead to different perceptions and ethics among sellers when making sales transactions or about something.